Internationalization & the Rise of Knowledge Society: What Aspects Countries Need to Consider? - Temtime, Meskerem Cheru (Advances in Social Sciences Research Journal, 2017)
The paper deals with important aspects countries need to consider in relation to internationalization & the rise of knowledge society. Along with this, three research questions such as What are the current patterns being observed in internationalization so far? What step must the government & HEIS take in order to facilitate internationalization & a better place in the knowledge society? What are the assumed benefits & the known challenges? are raised & discussed. For a clear understanding of the paper as a whole, basic terminologies such as internationalization & globalization, & levels at which HE internationalization works are discussed briefly based on literature outcomes. Finally, concluding remarks were put in place.